Socioemotional Wealth (SEW) of Family Firms and CEO Behavioral Biases in the Implementation of Sustainable Development Goals (SDGs) - Elżbieta Bukalska (MDPI AG, 2021)
Agreed upon by the UN member states, Agenda 2030 assumes joint action for long-term sustainable development. These actions are focused on the implementation of 17 Sustainable Development Goals (SDGs), where actions are assumed to lead to the suppression of negative externalities of human activity. It is stressed that the objectives of sustainable development can only be achieved through deep institutional changes in most dimensions of the economy, including the entrepreneurship dimension. Entrepreneurship plays a pivotal role in the sustainable transformation of the community, as the related activities of companies are the source of the desired structural changes. Entrepreneurial projects make the biggest contribution to the objectives of sustainable development through research and development, investment in new technologies, and innovation. The biggest threat to sustainable entrepreneurship is firms’ aggressive corporate financial strategy, which most often results from CEO overconfidence and aggressive financial behavior. The aim of the article is to indicate differences in corporate financial strategies regarding the status of the company (family or non-family) and CEO characteristics (overconfident or non-overconfident). The fulfilment of this aim by analyzing a selected EU member country (Poland) found more aggressive behavior of overconfident CEOs in non-family firms. It was also found that family firms are a fairly coherent group of companies that implement a more conservative corporate financial strategy regardless of CEO characteristics. We can state that family power can curb CEO overconfidence and its impact on aggressive financial strategy. This means that family firms are much more able to create sustainable entrepreneurship and contribute to Sustainable Development Goals (SDGs) within a market framework.